2020
DOI: 10.3389/fnmol.2020.00123
|View full text |Cite
|
Sign up to set email alerts
|

LAMA2-Related Dystrophies: Clinical Phenotypes, Disease Biomarkers, and Clinical Trial Readiness

Abstract: LAMA2-RD: Clinical Phenotypes and Biomarkers a five-year prospective natural history and comparative outcome measures study in patients with LAMA2-RD, have helped to better delineate the natural history and identify viable outcome measures. Plans for further clinical trials for LAMA2-RDs are presently in progress, highlighting the necessity of identifying adequate, disease-relevant biomarkers, capable of reflecting potential therapeutic changes, in addition to refining the clinical outcome measures and time-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 80 publications
4
72
0
1
Order By: Relevance
“…Although there are a few retrospective, cross-sectional studies exploring the natural history and genetic variations of LAMA2-related muscular dystrophy [4][5][6][7], long-term and large-scale studies of the natural history and genotype-phenotype correlations are limited. As promising therapeutic approaches (such as upregulation of LAMA1, mini-agrin, and laminin-α1 LN-domain nidogen-1 (αLNNd)) are getting closer to clinical application [9][10][11][12], the definition of natural history endpoints along with clinically relevant outcome measures is essential for both clinical care planning and clinical trial readiness [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a few retrospective, cross-sectional studies exploring the natural history and genetic variations of LAMA2-related muscular dystrophy [4][5][6][7], long-term and large-scale studies of the natural history and genotype-phenotype correlations are limited. As promising therapeutic approaches (such as upregulation of LAMA1, mini-agrin, and laminin-α1 LN-domain nidogen-1 (αLNNd)) are getting closer to clinical application [9][10][11][12], the definition of natural history endpoints along with clinically relevant outcome measures is essential for both clinical care planning and clinical trial readiness [13].…”
Section: Introductionmentioning
confidence: 99%
“…Cases of muscle weakness and altered energy metabolism, like those observed in OI patients and mouse models exhibiting type I collagen mutations, are also found in animal models and patients with muscular dystrophies possessing gene defects in extracellular matrix proteins such as laminin α2 ( LAMA2 ) and type VI collagen ( COLVI ) [ 47 , 48 ]. The clinical presentation of LAMA2-associated muscular dystrophies closely resembles that of the COLVI-related Bethlem myopathy, including muscle weakness, muscle hypotonia, and joint contractures [ 49 ].…”
Section: Skeletal Muscle Weakness and Energy Metabolism In Oimentioning
confidence: 99%
“…One study from 1998 analysed a small cohort of patients with merosindeficiency, assessing ID and MRI changes and concluded that in the presence of cerebellar hypoplasia, children frequently presented with lower IQs on performance [26] . It is striking that in several publications the genetic diagnosis remained unconfirmed by either a missing second mutation in LAMA2 or inconsistencies between laminin α2 expression and white matter changes [27] . Seizures are not primarily attributed to the white matter hypointensity found in LAMA2-CMD, but may be associated with additional cortical malformations or ventricular dilation [27] .…”
Section: Laminin α2 Chain Related Congenital Muscular Dystrophiesmentioning
confidence: 99%
“…It is striking that in several publications the genetic diagnosis remained unconfirmed by either a missing second mutation in LAMA2 or inconsistencies between laminin α2 expression and white matter changes [27] . Seizures are not primarily attributed to the white matter hypointensity found in LAMA2-CMD, but may be associated with additional cortical malformations or ventricular dilation [27] .…”
Section: Laminin α2 Chain Related Congenital Muscular Dystrophiesmentioning
confidence: 99%